Versorgung chronischer Schmerzen: Wirklichkeit und Anspruch = Chronic pain care : reality and entitlement - Kieselbach, Kristin; Schiltenwolf, Marcus; Bozzaro, Claudia (Der Schmerz, 2016)
From the point of view of healthcare policies, improvement in pain care has been required for years; however, there is a great discrepancy between the current need for pain care and the actual provision by healthcare services. This article seeks to demonstrate that while healthcare policies are one of the critical factors involved, a variety of conceptual, diagnostic and therapeutic causes should also be taken into account. Firstly, considering that pain care is primarily concerned with the suffering of pain by patients, the focus lies with their conscious experience in order to define the patients’ understanding of pain. Additionally, in this article current biomedical and psychosocial comprehension concerning chronic pain will be illustrated and why it is necessary to broaden our horizons in order to do justice to patients with chronic pain.
Gesehen am 06.12.2018